Discriminability of the Beck Depression Inventory and its Abbreviations in an Adolescent Psychiatric Sample - Seifi Fatemeh; Therman Sebastian; Tolmunen Tommi (Scandinavian Journal of Child and Adolescent Psychiatry and Psychology, 2025)
The Beck Depression Inventory (BDI) is a widely acknowledged self-report screening tool for evaluating the presence and intensity of depressive symptoms. The BDI-IA, although an older version, is highly correlated with the updated BDI-II, remains clinically valuable, and is widely used due to its free availability.